Sodium Sulfate (Na2SO4) Detection Using Graphene Coated Microfiber - Yasin, M; Pujiyanto, Pujiyanto; Anngita, D; Fanany, I A (Indonesian Applied Physics Letters, 2020)
We investigate the coating of graphene onto the silica microfiber sensor for sodium sulfate measurement at room temperature. The graphene obtained from graphene-polylactic acid filament was coated onto the microfiber based on drop casting methods. In this work, the graphene acts as cladding to interact with analyte as well as functions to trap either sodium cation or sulfate anion and increases the effective refractive index of the cladding. The sensor has  a good sensitivity of 0.82 dBm/% and resolution of 1.16 %. The sensitivity and resolution of the sensor were increased by the coating of graphene layer.